3R-CuCrO2 delafosite: crystal growth, crystal structure, dielectric and DC conductivity properties - Anton Matasov; Alexander Bush; Vladislav Kozlov; Adam Stash (Discover Materials)
Abstract Single-crystal samples of the 3R-CuCrO2 phase (R3m, a = 2.9613(2) Å, c = 17.098(2) Å) with a delafossite structure were grown by the flux method. Structural parameters were refined by X-ray structural analysis. The elemental composition of the grown crystals was confirmed by Auger electron spectroscopy. A threshold electric field switching effect from a high-resistance to a low-resistance state was discovered. The effect is characterized by a jump in electrical resistance (up to 5 orders of magnitude at E = 4.7 kV/cm, T = 120 K) and S-shaped current–voltage characteristics with a region of negative differential resistance. The temperature dependences of dielectric permittivity and dielectric loss tangent exhibit a Debye-type relaxation process with an activation energy of 0.51(3) eV. The observed features of dc conductivity, current–voltage characteristics, and dielectric properties interpreted on the basis of the existence of charge carriers in a small polaron state and the destruction of this state by the electric field.